Stage of the Analysis of the Crimean Khanate Sources: V.D. Smirnov » - A.A. Nepomnyashchiy (Золотоордынское обозрение)
On the basis of a substantial body of archival documents of the Institute of Oriental Manuscripts of the Russian Academy of Sciences and the little-known publications, the author has restored laborious work of professor of St. Petersburg University Vasiliy Dmitrievich Smirnov who collected, organized and preserved in the central archival repositories sources for the history of the Crimean Khanate. The author has reconstructed the main events in his life and his activities in the Imperial Public Library related to the concentration in this store of the Crimean Tatar documents (article also contains a short list of his main works). Not limited to the literary sources of Turkey and Russia, Vasiliy Dmitrievich repeatedly worked in the libraries of Budapest, Vienna, London, and Paris. In the 1880’s, he continued to develop the theme of his doctoral thesis and combined literary studies and work in the archives with archaeological researches in the Crimea. The author has analyzed the process of creating of the largest work on the history of the Crimean Khanate, which remains hitherto an unrivaled. V.D. Smirnov managed to summarize Turkish sources (medieval Ottoman and Crimean “chronicles”, most of which have not yet been translated) and historiography. This work continues to constitute a historiographical interest in the present. He widely covered, in the first place, the political history of the Crimean Khanate. The author have reviewed the research trip of V.D. Smirnov to the Crimea, his work in local archives, and communication with experts in the Crimean Tatar and Ottoman history. The author has considered the epistolary heritage of the scholar and, on this basis, discovered his academic contacts with leading researchers of Crimea of that time. The author found that he corresponded with such researchers as A.I. Markevich, N.A. Sultan Krym Giray, Z.A. Firkovich, S.M. Shapshal. To V.D. Smirnov belong a comprehensive source study on the history of medieval Turkey and its vassal, the Crimean Khanate.